EDUCATION AND NATIONAL IDENTITY – CROATIAN TEACHING ABROAD APPROACH - Kardum, Rona Busljeta (PUPIL: International Journal of Teaching, Education and Learning, 2024)
With the aim of preserving the Croatian national identity, the Ministry of Science and Education of the Republic of Croatia, in cooperation with 20 European and non-European countries, organizes, implements and finances (in full or in part) the special educational program Croatia Teaching broad. This specific form of education includes different dimensions: linguistic, historical, geographical, cultural, traditional, etc., and the mastering of content from the aforementioned areas contributes to the acquisition of knowledge about Croatia, the strengthening of language competences, a stronger connection with the homeland and the development of a sense of belonging to the Croatian people and culture. The research is focused on the comparison of Croatia’s approach to teaching abroad and the challenges of its realization, with regard to the number and status of Croats, historical specificities, geographical proximity, multilingual environments, intercultural communication, etc. Analysis of the differences between the countries where this form of teaching is carried out, will result in proposals for modular guidelines that would alleviate the perceived shortcomings.